Susceptibility of inbred mouse strains to infection with Serpula (Treponema) hyodysenteriae. - Nibbelink, S K (1991)
Several inbred strains of mice were inoculated with Serpula (Treponema) hyodysenteriae B204 to determine susceptibility to infection. Challenge doses of 10(7) or 10(8) spirochetes induced cecal lesions in C3H/HeJ mice and other C3H strains of mice. However, more than a 100-fold difference existed between the dose required to induce lesions in 50% of the infected C3H/HeJ mice (8.3 x 10(7)) and that required to induce them in 50% of the infected C3H/HeN mice (5 x 10(5)). C3H/HeJ mice lack a splenocyte mitogenic response to Escherichia coli lipopolysaccharide but exhibited a mitogenic response comparable to those of other C3H strains of mice when stimulated with S. hyodysenteriae endotoxin (butanol-water extract). Different inbred strains exhibited different susceptibilities to infection, with the strain C3H/HeN being the most susceptible on the basis of colonization and development of macroscopic cecal lesions. The ity gene had no apparent effect on susceptibility of mice challenged with S. hyodysenteriae. The involvement of the H-2 haplotype with susceptibility is unclear, but the mice bearing H-2k were more susceptible than mice with the H-2b, H-2d, or H-2q haplotype. These data support the hypothesis that the host's responsiveness to lipopolysaccharide influences the susceptibility to infection with S. hyodysenteriae. However, differences in susceptibility between inbred mice exist independent of the lps locus, suggesting that there are other inherent differences between mouse strains that affect susceptibility to infection by S. hyodysenteriae.